Transformation of State Administrative Law in the Digital Government Era - Sumardi Sumardi (Yayasan Adra Karima Hubbi, 2024)
Background: The rapid advancement of digital technologies has transformed various aspects of public administration, leading to the emergence of digital government. This shift necessitates significant changes in state administrative law to accommodate new modes of governance, service delivery, and citizen engagement. Objective: This study aims to examine the transformation of state administrative law in the context of digital government. The research seeks to identify the key legal adaptations required to support digital governance, enhance administrative efficiency, and ensure transparency and accountability. Methods: A mixed-methods approach was employed, combining qualitative and quantitative analyses. Qualitative data were collected through interviews with legal experts, public administrators, and policymakers to gain insights into the challenges and opportunities of digital government. Results: Findings indicate that significant legal reforms are necessary to support the transition to digital government. Key areas requiring adaptation include data protection and privacy, electronic records management, digital service delivery standards, and mechanisms for public participation. Survey results showed that both public officials and citizens recognize the benefits of digital government but also highlight concerns about data security and digital inclusivity. Conclusion: The transformation of state administrative law is crucial for the effective implementation of digital government. Legal frameworks must evolve to address the challenges posed by digital technologies while ensuring that governance remains transparent, accountable, and inclusive.